Management of Co-Curricular Activities in Fostering Global Diversity Character in Elementary Schools - Tegar Pambudhi; Sapriya; Kama Abdul Hakam; Wahyu Sopandi (LJPI UI Bunga Bangsa Cirebon, 2026)
Objective: This study aims to analyze the management of co-curricular activities in fostering the character of global diversity among primary school students. Global diversity is a key dimension of the Pancasila Student Profile, emphasizing cultural awareness, inclusive interaction, and fair behavior within a pluralistic society. Novelty: This research highlights systematic co-curricular management as a strategic mechanism for strengthening global diversity character within the implementation of the Merdeka Curriculum, particularly through the Pancasila Student Profile Strengthening Project (P5), where practical models at the school level remain varied and underexplored. Methods: The study employed a descriptive qualitative approach using interviews, observations, and document analysis. Data were analyzed through the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. Results: The findings reveal that effective co-curricular management depends on three main aspects: (1) needs-based and contextually relevant planning grounded in local culture, (2) collaborative and experiential learning activities that promote intercultural engagement, and (3) authentic evaluation emphasizing reflection, equitable participation, and inclusive contribution. Principal leadership, community partnerships, and teacher capacity were identified as key supporting factors. Conclusions: Co-curricular activities play a strategic role in shaping global diversity character among primary school students. Systematic and integrated management within the school ecosystem is essential to optimize their impact and achieve the goals of the Pancasila Student Profile.